Between Development and the State: Recasting South Korean Dirigisme - Park, Hun Joo (ASIAN JOURNAL OF POLITICAL SCIENCE, 2004)
This article offers an alternative understanding and a critique of how South Korea's development has been interpreted by various scholars. The proponents of developmental state overlook the fact that South Korean dirigisme harmed equity, democracy, social cohesion, and thus the people's ability to take the initiative and form a viable civil society. By considering how the state meddled with the economy as a deliberately selected course, an analysis can be made of the dysfunction of developmental statism or “diseased” dirigisme. The inequity between the deprivations suffered by small firm operators and other citizens and the gains reaped by a few business conglomerates (or chaebol), remains symptomatic of South Korea's dirigiste disease. The dominant themes in the current economic discourses are privatisation, marketisation, deregulation and the rolling‐back of the welfare state. However, liberalising the economy without state reform may aggravate the dirigiste disease in South Korea. By linking the state‐led and people‐centred arguments, this article provides a fresh discourse on principles of policy‐making and state‐action to broaden the valuation of development beyond economic efficiency or competitiveness.